Making and Characterization of Charcoal Briquettes from Palm Oil Shells and Hazelnut Shells - vika wahyu nadiana; irfandi irfandi (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2021)
Research has been conducted on The Manufacture and Characterization of Charcoal Briquettes From Palm Shells And Hazelnut Shells. This study aims to determine the influence of variations in the composition of palm shells and hazelnut shells on the calorific value, moisture content, and ash content in the resulting charcoal briquettes. This study was conducted by carbonization method, mixing, printing, drying and briquette youthfulness analyzed with test parameters namely moisture content, ash content, and calorific value. The results showed a mixture of palm shell and hazelnut shell can be used as briquettes. In this study briquettes with optimal composition were a mixture of variations of palm shell and hazelnut shell 60% : 35% with a moisture content of 6.25%, ash content of 11.37% and a calorific value of 5129.45 cal / gr.Keywords : Palm Shell, Hazelnut Shell, Moisture Content, Ash Content, Calorific    Value